The Effect of Competence, Organizational Culture and Work Ethic on Work Productivity - Nofriadi, Nofriadi; Rafki, Rafnelly; Oktarina, Yolanda (Dinasti Publisher, 2024)
Increased work productivity has significant implications for organizations, including revenue growth, greater profits, improved reputation, and the ability to attract and retain top talent. Therefore, companies are constantly striving to understand the factors that affect the work productivity of employees. The relationship between competence, organizational culture, work ethic, and work productivity is still an area of ever-evolving research. Therefore, this study aims to investigate and further understand how these variables interact and impact each other in an organizational context. The research method used is a quantitative survey study with the use of questionnaires as a data collection instrument. The research sample consisted of employees in various divisions of the company. The data were analyzed using multiple linear regression analysis. The results showed that competence, organizational culture, and work ethic have a positive and significant influence on work productivity. These findings support the alternative hypotheses proposed in the study. The implication of the results of this study is that organizations can increase work productivity by paying attention to employee competency development, strengthening organizational culture that supports performance, and encouraging a positive work ethic. This research makes an important contribution in understanding the factors that affect work productivity and provides a foundation for recommendations for improvement in the context of human resource management and organizational culture.